The Realization of Hedges and Boosters in Trump's and Clinton's Utterances in The US Presidential Debates in 2016 - Kusumawati, Henny; Rukmini, Dwi; Mujiyanto, Januarius (English Education Journal, 2021)
Hedges and boosters are crucial metadiscourse markers to soften and strengthen the proposition. Presidential candidates also rely on hedges and boosters to draw the publics' intentions. This study aims to explore the use of hedges and boosters in Trump's and Clinton's utterances in the US presidential debates in 2016. Accordingly, discourse analysis was adopted in this present study to find out the realization of types and functions of hedges and boosters as well as the differences and similarities of the occurrences of hedges and boosters between those two candidates based on the taxonomies of Salager-Meyer (1997), Demir (2017), Rabab'ah and Rumam (2015) and Hyland (2005). The strategy was elaborated into six sub-research questions to find out types, functions, differences, and similarities of hedges and boosters. The data were obtained from the transcript of the debates. The findings reveal that the seven types of hedges and six types of boosters were discovered in the utterances of Trump and Clinton. Associated with the functions of hedges and boosters, it shows that Trump and Clinton tend to use hedging devices to mitigate their claims by showing some kind of uncertainty. Boosters also applied to put emphasis on the value of the truth of their statements. It was discovered that Trump used more boosters and Clinton used more hedging devices as well.